Waste in the Nonprofit Sector in the Context of the 7+1 Muda Method - Kyć, Grzegorz; Piórkowska, Katarzyna (Marnotrawstwo w sektorze non-profit w kontekście METODY 7+1 Mud, 2025)
Aim: The paper aims to identify the manifestations of waste in non-governmental organizations based on the Lean Management philosophy, specifically 7+1 Muda. Methodology: To realise the research aim the narrative literature review was conducted. The examples of waste occurring in non-profit activities described in the literature were compared with its analogous examples occurring in for-profit activities and public institutions. Waste in non-profit organizations was also classified according to the categories described in the 7+1 Muda method. Results: The phenomenon of waste can have many forms, and being often hidden or unrecognised, it can negatively affect the activities of an NGO from operational and strategic perspectives. Waste in nonprofit organizations generally stems from structural, operational, and financial inefficiencies. Based on the 7+1 Muda framework, the key characteristics of waste in the non-profit sector may include: overproduction, overprocessing, excessive transportation, excessive inventory, motion waste, waiting time, defects, unused human potential (8th Muda). Implications and recommendations: this study may serve as a guide for nonprofits to identify and combat inefficiencies, ultimately leading to greater sustainability, improved impact, and better service to beneficiaries. By diagnosing waste within nonprofit activities, organizations can implement strategies to optimise processes, reduce unnecessary costs, and enhance overall performance. Additionally, the study provides insights into eliminating inefficiencies that drain financial assets and offers a framework for assessing waste in processes, allowing nonprofit leaders to make informed decisions on process improvements, resource distribution, and long-term sustainability. Originality/value: This article contributes to the discussion about the main causes of waste and its actual impact on non-governmental activities.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 3, s. 66-76